Comparative analysis of factor graph models for carrier phase-based precision navigation - Dome, Tibor; Russell, Theodore; Rejon, Miguel Ortiz; Zheng, Yuheng; Benedetti, Elisa; Li, Teng; Sun, Mengwei; Petrunin, Ivan (MDPI, 2026)
Factor graph optimization (FGO) has emerged as a powerful alternative to Kalman filtering for high-precision GNSS positioning, particularly under challenging conditions. Its modular structure allows for the seamless integration of motion constraints, ambiguity modeling, and multi-sensor data across diverse platforms and environments. This study reviews recent FGO architectures for high-precision GNSS methodologies (PPP, RTK), comparing ambiguity management strategies, measurement factor designs, and robust optimization techniques. We compare strategies for modeling ambiguities within the graph and evaluate how they interact with measurement factor design, cycle slip detection, and integer ambiguity resolution (IAR). Trade-offs in ambiguity management and optimization techniques are discussed to guide future design choices.
Keywords: PPP; RTK; factor graphs; integer ambiguity resolution